(untitled) (Medico Legal Update, 2021)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age, affecting 6%–10% of women worldwide. Objective: The study aimed to assess the relation of serum chemerin level with lipid profile in women with polycystic ovarian syndrome. Materials and Method: A cross?sectional study was carried out in Salah Al-din City from 10th of October 2019, to 20th of December 2019. The number of polycystic ovary syndrome women under study was 60 women whose ages were between 15 and 36 years old. These women admitted to obstetrics and gynecology unit at Salah Al-din Teaching Hospital. The control group who were matched to the patients studied included 30 women. Results: The study showed that there is the significant difference between PCOS women and the control group concerning serum chemerin level and lipid profile in PCOS women. This study demonstrates that there was a weak positive correlation between levels of chemerin and cholesterol in PCOS women (r = 0.02) which is mean that cholesterol level is slightly increased with the elevation of chemerin hormone in women with PCOS, There was a positive correlation between levels of chemerin and Triglyceride in PCOS women (r = 0.16) which is mean that level is slightly Triglyceride increased with the elevation of chemerin hormone in women with PCOS, There was a positive correlation between serum levels of chemerin and VLDL in PCOS women, slightly VLDL increased with the elevation of chemerin hormone in women with PCOS. There was a positive correlation between levels of chemerin and LDL in PCOS women, slightly LDL increased with elevation of chemerin hormone in women with PCOS. This study showed negative correlation between Chemerin and, HDL in PCOS women, slightly HDL decreased with the elevation of chemerin hormone in women with PCOS. Conclusion: Highly significant relation of Chemerin and Cholesterol,Triglyceride,LDLandVLDL in PCOS,While negative correlation between Chemerin and HDL